Evaluating scintillator performance in time‐resolved hard X‐ray studies at synchrotron light sources. (1st April 2016) - Rutherford, Michael E.; Chapman, David J.; White, Thomas G.; Drakopoulos, Michael; Rack, Alexander; Eakins, Daniel E.
Abstract : Scintillator performance in time‐resolved, hard, indirect detection X‐ray studies on the sub‐microsecond timescale at synchrotron light sources is reviewed, modelled and examined experimentally. LYSO:Ce is found to be the only commercially available crystal suitable for these experiments. Abstract : The short pulse duration, small effective source size and high flux of synchrotron radiation is ideally suited for probing a wide range of transient deformation processes in materials under extreme conditions. In this paper, the challenges of high‐resolution time‐resolved indirect X‐ray detection are reviewed in the context of dynamic synchrotron experiments. In particular, the discussion is targeted at two‐dimensional integrating detector methods, such as those focused on dynamic radiography and diffraction experiments. The response of a scintillator to periodic synchrotron X‐ray excitation is modelled and validated against experimental data collected at the Diamond Light Source (DLS) and European Synchrotron Radiation Facility (ESRF). An upper bound on the dynamic range accessible in a time‐resolved experiment for a given bunch separation is calculated for a range of scintillators. New bunch structures are suggested for DLS and ESRF using the highest‐performing commercially available crystal LYSO:Ce, allowing time‐resolved experiments with an interframe time of 189 ns and a maximum dynamic range of 98 (6.6 bits).